Does God Intend that Sin Occur? - Hart, Matthew J (Springer Nature, 2022)
This open access book argues, from a detailed consideration of the Christian Scriptures, that God intends that sin occur. It swims against the tide of current thinking in philosophy of religion, arguing for an unfashionable conclusion. The book begins by considering the history of views on the question, paying particular attention to the Reformed or Calvinistic tradition. The heart of the book is a detailed examination of key passages from the Christian Scriptures that, it is argued, show that God does intend that sin occur. It also discusses in detail two alternative views that could be used to reinterpret these texts, one view that God intends only that the substratum of the sinful action occur, not the sin itself, and the other that God acts because a sin will occur but not intending that that sin occur. The book argues that these interpretative strategies, even when combined together, do not produce a plausible interpretation of the texts adduced.